1986
DOI: 10.1017/s0047404500012008
|View full text |Cite
|
Sign up to set email alerts
|

The spontaneous use of thank you by preschoolers as a function of sex, socioeconomic status, and listener status

Abstract: This study investigated whether preschoolers would spontaneously say thank you in a familiar context without their parents' presence. Two hundred and fifty 3 1/2-to 4 1/2-year-olds played a game with their teachers and received a reward from either an unfamiliar peer or adult. Across conditions, 37 percent of the children said thank you spontaneously, more than in previous studies. The frequency of the spontaneous use of thank you was assessed as a function of sex, socioeconomic status, and listener status. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 15 publications
4
32
0
5
Order By: Relevance
“…When examining the sub-categories of hedonistic wishes we found that, in public schools at least, boys were more likely to wish for money and material things than were girls; this is in accord with previous research in the United States that suggested that boys are more materialistic than are girls (Goldberg et al, 2003;Kasser, 2005). Finally, regarding gender differences in the expression of gratitude, the findings of this study suggest that public school girls expressed somewhat more verbal gratitude than did their male counterparts, a finding in keeping with those who suggest that females may be more likely to say "thank you" than are males (Becker & Smenner, 1986;Gordon et al, 2004;Kashdan et al, 2009). It is interesting that some gender differences were more prominent among students from public schools in comparison to students from private schools.…”
Section: Discussionsupporting
confidence: 89%
“…When examining the sub-categories of hedonistic wishes we found that, in public schools at least, boys were more likely to wish for money and material things than were girls; this is in accord with previous research in the United States that suggested that boys are more materialistic than are girls (Goldberg et al, 2003;Kasser, 2005). Finally, regarding gender differences in the expression of gratitude, the findings of this study suggest that public school girls expressed somewhat more verbal gratitude than did their male counterparts, a finding in keeping with those who suggest that females may be more likely to say "thank you" than are males (Becker & Smenner, 1986;Gordon et al, 2004;Kashdan et al, 2009). It is interesting that some gender differences were more prominent among students from public schools in comparison to students from private schools.…”
Section: Discussionsupporting
confidence: 89%
“…Verbal gratitude is the simplest form, and is found in children as young as 3 (Becker & Smenner, 1986). It is difficult, however, to distinguish verbal gratitude from politeness.…”
Section: Discussionmentioning
confidence: 99%
“…In general, women are slightly more likely than men to experience and express gratitude (Becker and Smenner 1986;Emmons 2004;Froh et al 2009;Gordon et al 2004;Ventimiglia 1982). However, most of the existing scholarship does not focus on factors that predict gratitude.…”
mentioning
confidence: 99%